(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2018)
This article investigates the poetry of the Mexican movement “Infrarealism”, as well as its main aesthetics and literary influences, both national and international. In order to do so, Roberto Bolaño’s novel, The savage detectives, is analyzed as an selfcritical rewriting realized by the author to his own poetic project, several years after its failure in his attempt to fuse art and life.